Understanding Prolepsis through Teacher Research - Phillip White (Networks: An Online Journal for Teacher Research, 1998)
Most often teacher research is written in a linear narrative form, bringing the reader along the story line of discovery much as the researcher herself made her discoveries. I have chosen a different approach, one I'll label as recursive narrative. This narrative form follows my own thinking processes, reflexive, discursive, moving recursively from present to future to past and back again, attempting to create a circular whole that is evident at the end. This recursive narrative form is reflective of the shape of prolepsis itself, analyzing an activity while taking into account its historical form, its present form, and considering what its future form might look like, in order to decide what to do next. I believe that all teachers view their classroom activities proleptically, but have not made such thinking explicit to themselves. What follows is a recursive description about how I have attempted to make my proleptic thoughts explicit.